Effect of gamma irradiation on the size of cellulose nanocrystals with polyethylene glycol and sodium hydroxide/Gd2O3 nanocomposite as contrast agent in magnetic resonance imaging (MRI) - Whba, Fathyah (Korean Nuclear Society, 2024)
The attractive properties of gadolinium-based nanoparticles as a positive contrast agent for magnetic resonance imaging (MRI) have piqued the interest of both researchers and clinicians. Nonetheless, due to the biotoxicity of gadolinium (III) ions' free radicals, there is a need to address this issue. Therefore, this research aimed to develop a biocompatible, dispersible, stable, hydrophilic, and less toxic cellulose nanocrystals/gadolinium oxide nanocomposite as contrast agent properties for MRI purposes. This study aimed to synthesize gadolinium oxide nanoparticles coated with cellulose nanocrystals with polyethylene glycol and sodium hydroxide (CNCs-PEG/NaOH)/Gd2O3 using the gamma irradiation method to reduce the particle size. The results showed that using a gamma irradiation dose of 10 kGy, quasi-spherical morphology with a size of approximately 5.5 ± 0.65 nm could be produced. Furthermore, the cytocompatibility of (CNCs-PEG/NaOH)/Gd2O3 nanocomposite synthesized was assessed through MTT assay tests on Hep G2 cells, which demonstrated good cytocompatibility without any cytotoxic effects within a concentration range of (10 μg/mL −150 μg/mL) and had sufficient cellular uptake. Moreover, the T1-weighted MRI of (CNCs-PEG/NaOH)/Gd2O3 nanocomposite revealed promising results as a positive contrast agent. It is envisaged that the gamma irradiation method is promising in synthesizing (CNCs-PEG/NaOH)/Gd2O3 nanocomposite with nanoscale for different applications, especially in the radiotherapy field.